Mahuang Decoction Attenuates Airway Inflammation and Remodeling in Asthma via Suppression of the SP1/FGFR3/PI3K/AKT Axis - Wei L; Gou X; Su B; Han H; Guo T; Liu L; Wang L; Zhang L; Chen W (Dove Medical Press, 2022)
Lina Wei,1 Xulei Gou,2 Baoning Su,3 Haiqiong Han,4 Tingting Guo,5 Liang Liu,5 Lei Wang,5 Lina Zhang,3 Weibin Chen6 1Children's Medical Center, Affiliated Hospital of Changchun University of Traditional Chinese Medicine, Changchun, 130021, People's Republic of China; 2Department of Pediatrics, Beijing Daxing District Maternal and Child Health Care Hospital, Beijing, 102600, People's Republic of China; 3Department of Pediatrics, Shanghai Jiading Traditional Chinese Medicine Hospital, Shanghai, 201800, People's Republic of China; 4Department of Rehabilitation Medicine, Community Health Service Center of Jiangqiao Town in Jiading District, Shanghai, 201803, People's Republic of China; 5Changchun University of Traditional Chinese Medicine, Changchun, 130017, People's Republic of China; 6Department of Pediatrics, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200437, People's Republic of ChinaCorrespondence: Lina Zhang, Department of Pediatrics, Shanghai Jiading Traditional Chinese Medicine Hospital, No. 222, Bole Road, Jiading District, Shanghai, 201800, People's Republic of China, Tel +86-18930568760, Email lina1988zhang@163.com Weibin Chen, Department of Pediatrics, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, No. 110, Ganhe Road, Hongkou District, Shanghai, 200437, People's Republic of China, Tel +86-18621863233, Email weibin1965chen@163.comBackground/Purpose: Mahuang decoction (MHD) is a classic famous traditional Chinese medicine and has various pharmacological effects, including anti-inflammation and anti-asthma. In this study, we aimed to investigate the potential protective effect of MHD against asthma and elucidated the underlying mechanism.Materials and Methods: A mouse model of asthma was induced by ovalbumin (OVA) treatment, and then treated with MHD to evaluate its effect on the asthma. Gain- or loss-of-function approaches were performed in SP1 and FGFR3 to study their roles in asthma via measurement of airway inflammation, airway remodeling and airway smooth muscle cell (ASMC) proliferation-related factors.Results: MHD reduced airway inflammation and remodeling. Additionally, MHD contributed to diminished expression of SP1, which was shown to repress airway inflammation and remodeling. Furthermore, SP1 bound to the FGFR3 promoter, resulting in the FGFR3 transcription promotion and ASMC proliferation. Conversely, FGFR3 knockdown abolished airway inflammation and remodeling, the mechanism of which was related to suppression of the PI3K/AKT signaling pathway. Meanwhile, MHD hindered airway inflammation and remodeling following asthma by suppressing the SP1/FGFR3/PI3K/AKT axis.Conclusion: Taken together, MHD may retard airway inflammation and remodeling by suppressing the SP1/FGFR3/PI3K/AKT axis, which contributes to an extensive understanding of asthma and may provide novel therapeutic options for this disease.Keywords: Mahuang decoction, asthma, SP1, FGFR3, PI3K/AKT signaling pathway, airway inflammation, airway remodeling